Determinants of Parental Guidance of Children's Television Viewing: A Dutch Replication Study - van der Voort, Tom H. A (Journal of broadcasting & electronic media, 1992)
Dutch replication of Bybee, Robinson and Turow's 1982 study of parental influence on television viewing by children between 3 and 18 years old found 3 distinct parental models: restrictive, evaluative, and unfocused guidance. Parental attitudes toward television and its effects on children were found to be important determinants in the type of guidance offered. (22 references) (LAE)